Overweight Handbook Increases Physical Activity of Students at Frater Junior High School, Kendari - Ellyani Abadi (KLASICS, 2021)
Abstract. The prevalence of overweight in adolescence at junior high (SMP) school Frater was 14.1% (exceeded the standard of the nutritional problem for 10%), and thus requires innovation in form of a handbook to overcome the obesity problem. This study aimed to know the effect of the overweight handbook on the physical activity in adolescents at SMP Frater Kendari. This was a quantitative study (pre-experimental study) with a pre-test post-test study design that was done from 7 May-14 July 2018. The population of the study was all students with overweight status at SMP as many as 38 people and the samples were 32 students that were selected through a simple random sampling. The physical activity level was assessed using IPAQ for 4 times and analyzed using the Wilcoxon sign rank test. The results of the study showed that the average METs score of the activity level in pre-measurement was 280 METs per week and the post-measurement 669 METs per week. Meanwhile, the result of the paired t-test on physical activity showed p value (0.000)<α (0.05). This present study concludes that there is an effect of the overweight handbook to the increase on physical activity level of the adolescents. It is suggested to the overweight student at SMP Frater to read the handbook regularly and increase their activity level by exercising at least 30 minutes for 2 -3 times per week and to the school party, to educate the student routinely about overweight using the handbook.